TEACHER ADAPTATIONS OF SCIENCE PROCESS SKILLS (SPS) IN JUNIOR HIGH SCHOOL 1 SIDOARJO DURING THE COVID-19 PANDEMIC - Adinda Arlin Husniyyah; Erman Erman (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
This study aimed to identify the teacher adaptation of Science Process Skills (SPS) implementations during the Covid-19 pandemic. This study uses multiple case studies. The subjects were three science teachers and fifteen students 7th grade from JHS 1 Sidoarjo. The instrument of this study consists of teacher and student questionnaires with the data collection techniques used the descriptive of observation, interviews, and documentation. The result showed that all of the teacher have changed their lesson plan and student worksheet for adjustment to online learning but it still used the SPS activities, but some SPS indicators can't be implemented properly. Teacher adaptations for the SPS during online learning are 1) improve the ability for use technology with applications used as learning media; 2) simple observation with uncomplicated tools and safety; 3) giving and collecting assignments by applications and presenting; 4) giving stimulus in the form of problems using images/videos to formulate hypotheses and variables before do the experiments, then presenting and analyzing the data individually at home. The results of this study are used as reference for all science teachers to coordinate on the selection of the right SPS activities, so all of the SPS indicators can be implemented optimally.